Endoscopic full-thickness resection for T1 early rectal cancer: a case series and video report - Soriani, Paola; Tontini, Gian Eugenio; Neumann, Helmut; de Nucci, Germana; De Toma, Domenico; Bruni, Barbara; Vavassori, Sara; Pastorelli, Luca; Vecchi, Maurizio; Lagoussis, Pavlos (Endoscopy International Open, 2017)
Background and study aims Endoscopic treatment of malignant colorectal polyps is often challenging, especially for early rectal cancer (ERC) localized close to the dentate line. Conversely, the surgical approach may result in temporary or definitive stoma and in frequent post-surgical complications. The Full-Thickness Resection Device (FTRD®) System (Ovesco Endoscopy, Tübingen, Germany) is a novel system that, besides having other indications, appears to be promising for wall-thickness excision of intestinal T1 carcinoma following incomplete endoscopic resection. However, follow-up data on patients treated with this device are scarce, particularly for ERC.Patients and methods Six consecutive patients with incomplete endoscopic resection of T1-ERC were treated with the FTRD and their long-term outcomes were evaluated based on a detailed clinical and instrumental assessment.Results The endoscopic en bloc full-thickness resection was technically feasible in all patients. The histopathologic analysis showed a complete endoscopic resection in all cases, and a full-thickness excision in four. Neither complications, nor disease recurrence were observed during the 1-year follow-up period.Conclusions The FTRD System is a promising tool for treating ERC featuring a residual risk of disease recurrence after incomplete endoscopic mucosal resection in patients unfit for surgery or refusing a surgical approach.